Case report: serologic investigation of canine coronavirus presence in a dog shelter - Sibel Gür; Turan Civelek (Eurasian Journal of Veterinary Sciences)
In this study, the presence of canine coronavirus infection (CCoV) was serologically investigated in a dog shelter where an infection with dehydration, severe hemorrhagic gastroenteric and high mortality in puppies were observed in Bursa region. Blood samples were obtained from 23 adult female dogs which lost ail or a few of their puppies and from 36 puppies which were recovered Irom the infection or had continuous diarrhoea, As a typical autopsy findings, hemorrhagic gastroenteritis were noted in all dead puppies. According to the indirect ELISA test results all adult dog and 34 out ol 36 puppies were found to be positive lo CCoV antibodies. (57 / 59). Clinically and serologically CCoV infection was identified in puppies in the shelter and it was determined that the seroposilıvıty of CCoV infection was %96.6.